ANALISIS LAYANAN JAKARTA SIAGA 112 DALAM MENDUKUNG PENANGANAN BENCANA DI DKI JAKARTA - Febi Dwi Putri; Fauzi Bahar (Republic of Indonesia Defense University, 2020)
Nowadays, non-military threat like a disaster is annually increasing in Indonesia. DKI Jakarta as capital city of Indonesia face multi-hazard risk such as urban flood, earthquake, land slide, urban fire and also social conflict. The high population density increase the vulnerability of DKI Jakarta. To deliver a quick emergency response, DKI Jakarta needs an integrated emergency communication system which is help government to relieve an emergency state immediately. DKI Jakarta on October 2016 has launched Layanan Jakarta Siaga (LJS) 112 as integrated emergency communication system which is can be used by community to inform their emergency needs and to obtain the information from government. This research aimed to analysis management and achievement of LJS 112 in supporting disaster management in DKI Jakarta. This research used qualitative research with study case approach conducted at BPBD DKI Jakarta. Participants was selected through purposive sampling and data was collected through depth interview, document study, and audio-visual material which analyzed using qualitative analysis technique. The result showed that LJS 112 has good management but has not have good organizational planning yet. LJS 112 performance showed by SLA (Service Level Agreement) with target 95% succesfully achieved by LJS 112. LJS 112 has significant function to lead the coordination for all public sector who are involved in LJS 112 system. LJS 112 in supporting disaster management ought to have good organizational planning, created measurable performance indicators and maximize the organization functions as a coordination center in the event of a disaster in Jakarta.